DNA Binding and Oxidative Cleavage Studies of Supramolecular Copper(II) Complex Based on b-Cyclodextrin - Tang, Si-Ping; Feng, Yong-Lan; Xu, Zhi-Feng; Wang, De-Ping (Asian Journal of Chemistry, 2013)
A copper(II) complex (CuL, 1) with aminothioether ligand and its new inclusion complex with b-cyclodextrin (CuL/b-CD, 2) have been prepared successfully. The binding modes of both complexes with calf thymus DNA were investigated by UV-visible and circular dichroism spectroscopies. Results show that both complexes mainly adopt electrostatic attraction binding mode with DNA and binding constants are (2.02 ± 0.02) × 103 and (1.79 ± 0.05) × 103 M-1, respectively. Both complexes are able to cleave pBR322 plasmid DNA efficiently in the presence of ascorbic acid and the activity of 2 is higher than that of 1. The DNA cleavages by 1 and 2 were inhibited strongly in the presence of DMSO and tert-butyl alcohol, which suggests that hydroxyl radicals are reactive oxygen species for the cleavage.